Spectrum of HRCT Chest Findings in RT-PCR Positive Asymptomatic COVID-19 Patients at a COVID Designated Hospital in Nepal - Basnet, Bina; Pant, Sujit; Shahi, Rajive Raj; Rai, Kalpana; Tulachan, Niraj; Thapa, Bikash Bikram (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: COVID-19 pandemic is grappling the world with the surge of infection time and again. Clinicians are trying to justify the ethics of public health care. Asymptomatic COVID-19 cases are going undocumented and most of them practice self-isolation. Studies have revealed significant radiological changes among RT-PCR positive asymptomatic COVID-19 cases. The aim of this cross-sectional study was to characterized chest CT findings of asymptomatic RT-PCR-positive patients in one of the COVID-designated hospitals in Nepal. Methods: This was a cross-sectional observational study where RT-PCR positive COVID-19 asymptomatic-close-contacts were subjected to HRCT chest. The HRCT images were evaluated by two radiologists for (a) characterizing the parenchymal involvement and (b) distribution of the involvement. The CT severity score (0-25) was calculated following the semi- quantitative scoring system which depends on the visual assessment of five lung lobes. Results: Out of 43, 26 (60.5%) participants had positive Chest CT scan findings consistent with COVID pneumonia. Bilateral lesions were present in 65% and 77% had multifocal lesions. The ground-glass opacities (92%), mixed (ground-glass opacities and consolidation pattern) (30.7%), and consolidation only (34.6%) were common chest CT findings. The median CT score was 3.5 (IQR; 2-6). Conclusion: Most of the RT-PCR positive COVID-19 asymptomatic patients had CT scan changes in lungs but with lower median CT score value.